Driving the Initiative of Service-Oriented Architecture Implementation - Sulong, Muhammad Suhaizan; Koronios, Andy; Gao, Jing; Abdul-Aziz, Azlianor (IBIMA Publishing, 2012)
Over the years, many organisations have invested heavily in information systems, changing the way they do business for improvement. Today however, aligning business and information systems is not easily achieved due to rapidly changing business environment. The ability of an organisation to change and change quickly in response to business needs is of paramount concern. This means the current traditional approach of adopting information systems is not suitable. Thus, a need of new paradigm to make business more agile and flexible is undeniable. The new paradigm is that taking a service-oriented architecture initiative as an enabling technology for critical business processes. This review paper has identified a distinctive approach compared to traditional information systems, a generic initiative process as well as the success factors of implementing the service-oriented architecture initiative. Further work is required through case study to obtain insightful understanding on any related issues and challenges in order to build better solutions for such initiative.